Addressing Charge‐Transfer and Locally‐Excited States in a Twisted Biphenyl Push‐Pull Chromophore. Issue 21 (11th September 2019) - Campioli, Elisa; Sanyal, Somananda; Marcelli, Agnese; Di Donato, Mariangela; Blanchard‐Desce, Mireille; Mongin, Olivier; Painelli, Anna; Terenziani, Francesca
Abstract: We present the synthesis and spectroscopic characterization of a twisted push–pull biphenyl molecule undergoing photoinduced electron transfer. Steady‐state and transient absorption spectra suggest, in this rigid molecular structure, a subtle interplay between locally‐excited and charge‐transfer states, whose equilibrium and dynamics is only driven by solvation. A theoretical model is presented for the solvation dynamics and, with the support of quantum chemical calculations, we demonstrate the existence of two sets of states, having either local or charge‐transfer character, that only "communicate" thanks to solvation, which is the sole driving force for the charge‐separation process. Abstract : With the help of solvation : The photoinduced, solvent‐driven intramolecular electron transfer is followed in real time, demonstrating the existence of two mutually‐orthogonal sets of locally‐excited and charge‐transfer states.